Overview of the 2022 Annual Trends and Outlook Report (ATOR) - Tadesse, Getaw (2023)
Getaw Tadesse POLICY SEMINAR Taking Stock of Africa’s Agrifood Processing Sector Key findings of the 2022 ReSAKSS Annual Trends and Outlook Report on Agrifood Processing Strategies for Successful Food Systems Transformation in Africa Co-organized by IFPRI and Akademiya2063 FEB 9, 2023 - 8:00 TO 9:30AM EST